African Philosophers and the Quest for Development in Contemporary Africa - Ademowo, Adeyemi Johnson (Àgídìgbo: ABUAD Journal of the Humanities, 2013)
The tasks for African philosophers in crisis-ridden Afri a is the focus of this work. It examines the effect of the three decades debate on the existence, 'who is', as well as 'who is not', an African Philosopher on how they define their roles in channeling a path for African growth and development. It argues that the debate, while vital to the philosophical enterprise, need not distract those that claimed to be 'philosophers' or with 'Philosophy degrees' from contributing their quota to the discourse on African development. It ends by outlining the role(s) that contemporary African philosophers should play, both for the sake of relevance and justification of devoting hours to contemplations and rigorous thinking.